Zbirka nalog iz strojnih elementov: zobniška gonila - Ren, Zoran; Glodež, Srečko; Belšak, Aleš (2017)
Collection of Exercises in Machine Elements Gear Units. Collection of Exercises in Machine Elements – Gear Units includes selected practical exercises in the field of calculation of gear units with cylindrical, bevel and worm gear pairs. The collection is a supplement to the University textbook with the title: Glodež S., Ren Z., and Flašker F., Strojni elementi – Zobniška gonila : University textbook. Faculty of Mechanical Engineering, University of Maribor, 2008. The textbook is urgently required to enable an effective use of the Collection of Exercises as all the designations, equations, figures, tables and diagrams referred to in the text without specified source are taken from the mentioned textbook. The purpose of the Collection is to help students with theoretical exercises and seminar papers, and to enhance their preparation for the written part of the exam in Machine Elements and for related exams. Owing to up-to-date calculation methods it is suitable also for the use in general mechanical engineering practice.
Keywords: gear units; cylindrical gears; bevel gears; worm gears; solved exercises